Use of Mendelian Randomization for Identifying Risk Factors for Brain Tumors - Howell, Amy Elizabeth; Zheng, Jie; Haycock, Philip C.; McAleenan, Alexandra; Relton, Caroline; Martin, Richard M.; Kurian, Kathreena M. (Frontiers in Genetics, 2018)
Gliomas are a group of primary brain tumours, the most common and aggressive subtype of which is glioblastoma. Glioblastoma has a median survival of just 15 months after diagnosis. Only previous exposure to ionizing radiation and particular inherited genetic syndromes are accepted risk factors for glioma; the vast majority of cases are thought to occur spontaneously. Previous observational studies have described associations between several risk factors and glioma, but studies are often conflicting and whether these associations reflect true casual relationships is unclear because observational studies may be susceptible to confounding, measurement error and reverse causation. Mendelian randomization (MR) is a form of instrumental variable analysis that can be used to provide supporting evidence for causal relationships between exposures (e.g. risk factors) and outcomes (e.g. disease onset). MR utilises genetic variants, such as single nucleotide polymorphisms (SNPs), that are robustly associated with an exposure to determine whether there is a causal effect of the exposure on the outcome. MR is less susceptible to confounding, reverse causation and measurement errors as it is based on the random inheritance during conception of genetic variants that can be relatively accurately measured. In previous studies, MR has implicated a genetically predicted increase in telomere length with an increased risk of glioma, and found little evidence that obesity related factors, vitamin D or atopy are causal in glioma risk . In this review we describe MR and its potential use to discover and validate novel risk factors, mechanistic factors, and therapeutic targets in glioma.